Application of ZnO Semiconductor Nanomaterial Ink in Packaging and Printing Design - Changjian Guo (Journal of Chemistry)
In order to obtain a flat and clear packaging printing pattern, the author proposes a printing method based on ZnO semiconductor nanomaterial ink. The method uses zinc acetate dihydrate as raw material, ethylenediamine as a complexing agent, absolute ethanol as a solvent, and ethyl cellulose as an auxiliary agent to prepare particle-free ZnO functional ink. The ink was spin-coated on a glass substrate, cured at different temperatures on a heating plate for 30 min, and passed through an X-ray diffractometer, a field emission scanning electron microscope, an infrared spectrometer, a synchronous thermal analyzer, an ultraviolet-visible spectrophotometer, and a transmission electron microscopy were used to characterize the synthesized inks and the resulting films. Experiments show that the decomposition temperature of particle-free ZnO conductive ink is much lower than that of zinc acetate precursor; the film cured at 300°C for 30 min has a smooth surface, uniform particle size, good crystallinity, and transmittance of up to 80%. After inkjet printing on the PI flexible substrate, after curing at 300°C for 30 min, the pattern surface is smooth and clear, and the outline is clear. Conclusion. The printing method is based on ZnO semiconductor nanomaterial ink. It has good application prospects in packaging and printing design.